Hizbullah, Libanon und Israel - Koch, Anne (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2006)
This paper looks at the recent military confrontation between Israel and Hezbollah in the Lebanese-Israeli border region. It describes the constitution of Hezbollah as a consequence of the regional and Lebanese context and points at the impossibility of disarming Hezbollah by external forces. There exist a number of unsolved issues in this contentious frontier area, i.e. the Israeli claim for the Lebanese water resources or the occupation of the Syrian Golan Heights. These issues have to be solved in advance to prepare the ground for an internal national Lebanese dialogue and consensus regarding the disarming of Hezbollah.